Innate Immune Sensors and Cell Death—Frontiers Coordinating Homeostasis, Immunity, and Inflammation in Skin - Ye Mon Soe; Seen Ling Sim; Snehlata Kumari (Viruses)
The skin provides a life-sustaining interface between the body and the external environment. A dynamic communication among immune and non-immune cells in the skin is essential to ensure body homeostasis. Dysregulated cellular communication can lead to the manifestation of inflammatory skin conditions. In this review, we will focus on the following two key frontiers in the skin: innate immune sensors and cell death, as well as their cellular crosstalk in the context of skin homeostasis and inflammation. This review will highlight the recent advancements and mechanisms of how these pathways integrate signals and orchestrate skin immunity, focusing on inflammatory skin diseases and skin infections in mice and humans.